The Influence of Limited Face-Face Learning on Student Learning Effectiveness in Fiqih Subjects - Umar Rosadi; M Aditya Firdaus; Raden Syara (Edumaspul: Jurnal Pendidikan, 2022)
The objectives of this study were: 1) to find out the reality of face-to-face learning limited to class VIII Fiqh subjects at MTs YPP Sukamiskin Bandung; 2) To find out the effectiveness of student learning in class VIII fiqh subjects at MTs YPP Sukamiskin Bandung. 3) Examine only the effectiveness of student learning in Fiqh Class VIII at MTs YPP Sukamiskin Bandung to determine the effect of face-to-face meetings on student learning.The method used in this research is a descriptive method with a quantitative approach. The techniques or methods of data collection used in this study were questionnaires, observation, and document studies. In taking the sample, we used purposive cluster random sampling. The data analysis technique used in this research is instrument analysis, the classic assumption test, descriptive statistics, and the t test for hypothesis testing. To find out the influence of the learning effectiveness variable on private madrasah tsanawiyah students when face-to-face learning is limited to student learning effectiveness, the researcher used a simple linear regression analysis. The results in this study are as follows: 1) The results of the descriptive statistical test on variable X get an average result of 53.90, with the most answers being "strongly agree." 2) The results of the descriptive statistical test on variable X give an average result of 57.80, with the most answers agreeing. 3) Based on the analysis conducted, the coefficient value of the independent variable is positive, which means that limited face-to-face learning has a positive effect on student learning effectiveness of 21.5% (very weak).